Management of Inflammatory Internal Root Resorption with Biodentine and Thermoplasticised Gutta-Percha - Girish Umashetty; Upendra Hoshing; Suvarna Patil; Nishant Ajgaonkar (Case Reports in Dentistry)
Internal root resorption is a chronic inflammatory process initiated within the pulp space with the loss of dentin. This condition demands a comprehensive understanding of the pathologic process, so as to identify the cause and arrest the resorptive phenomena. It is a rare occurrence, asymptomatic, with slow progression, detected through routine radiographic examination, where it appears as a radiolucent lesion. This paper reports a clinical case of inflammatory internal root resorption in the premolar tooth. Because it is asymptomatic, internal root resorption needs an early diagnosis in order to institute the endodontic treatment before the process compromises the remaining mineralized structures of the tooth. Biodentine was used to reinforce the weaker structures in the root. Thermoplasticised gutta-percha was used to completely obturate the defect. Ten-month follow-up showed arrest of internal root resorption.